The influence of agrotechnical techniques on the accumulation of sugars in the stems of sugar sorghum in the conditions of the Lower Volga Region - E. N. Efremova; A. I. Belyaev; N. I. Petrov (Новые технологии)
Sugar sorghum is mainly used for green fodder, haylage and silage. The accumulation of sugars occurs throughout the growing season. The relevance of the study is to identify a high-yielding variety or hybrid of sugar sorghum containing a large amount of sugars, which are later used for the manufacture of feed. The purpose of the study: to assess the impact of agrotechnical techniques on the feed evaluation of sugar sorghum. Tasks: to consider the dynamics of the accumulation of sugars in the stems of sugar sorghum; to calculate the yield of sugar from the stems of sugar sorghum; to determine the biochemical composition and gross energy of the green mass of sugar sorghum. The experience is three-factor in four-fold repetition. The experimental fi were located in the LLC “Kuznetsovskaya” Agricultural Complex of the Ilovlinsky district. The research period is 2009...2015. The research provided for the study of the nutritional value of sugar sorghum (crude protein, fat, protein, sugar, BEV). When determining the dynamics of the accumulation of sugar sorghum, the best indicator was on the variant of the joint use of the biostimulator of growth Lignohumate and mineral fertilizer on the hybrid Slavyansk homestead. For dump tillage, the average accumulation of sugars on this hybrid varied from 5.5 to 18.4% of dry matter, for zero tillage – 6.1 to 18.65%. The amount of sugar yield was influenced by the yield and concentration of sugars in the stems. The largest content was on the hybrid Slavic household. For dump and zero tillage, the best option was against the background of the combined use of a growth biostimulator and mineral fertilizer, amounting to 11.3 and 13.3 t/ha, respectively. When further determining the biochemical composition of sorghum, the best indicators for the content of crude protein, fat, fi  and ash were on the Debut variety. On the Slavic fi   VS variety and the Slavic homestead hybrid, these indicators had average values. The amount of nitrogen-free extractive substances contained more on the Slavic homestead hybrid, averaging 64.9%.